Low Cost Maximum Power Point Tracking Method For Solar Battery Charging - Koral, Ahmet Can; Bilgiç, Mehmet Oruç; GÜRKAN, GÜRAY (IEEE, 2013)
In this paper, we propose a low cost charger circuit with a maximum power point tracking method (MPPT) that is a key factor in photovoltaic systems. The solar panel output voltage, which is known to be generated by series connected solar cells (also called as photovoltaic cells), was adjusted to a constant voltage to maximize the transferred power even at different intensities of sunshine. By modifying the feedback circuit of a commercially available buck converter, we managed to constantly adjust the operating voltage of the solar panel to its point of maximum power being a different version of maximum power point tracker.
Keywords: Maximum power point trackers; Batteries; Photovoltaic cells; Photovoltaic systems; Integrated circuit modeling; Arrays